Assessment of gas explosion risk in underground spaces adjacent to a gas pipeline. (January 2023) - Li, Yuanzhi; Qian, Xinming; Zhang, Shuyu; Sheng, Jiaojiao; Hou, Longfei; Yuan, Mengqi
Highlights: A method to quantitatively evaluate underground spaces explosion risk was established. The flame and fragment damage assessment model were established based on a full-scale explosion experiment. The probability of gas diffusion and gathering was calculated using the micro-element method. Abstract: With the increased number and scale of gas pipelines, gas explosions in underground spaces adjacent to pipelines occur occasionally. A method was proposed in this study for evaluating the explosion risk in underground spaces adjacent to gas pipelines. The method was established on the basis of a full-scale independent underground space (IUS) explosion experiment and the whole-chain accident evolution model of "leak-diffused aggregation-ignition-explosion, " which consists of the possibility, consequence, and correction factors of an underground space explosion was proposed. Explosion possibility assessment included pipeline leakage, diffusion aggregation, and ignition probabilities. In particular, the diffusion aggregation probability assessment method, as the focus here for explosion possibility assessment, was proposed based on the method of micro-elements and behavior of gas diffusion in soil. A manhole explosion experiment was carried out for IUS explosion consequence assessment, including the extent and intensity of explosion flame, overpressure, and debris effects. The experiment also confirmed the conclusion that the explosion overpressure of the manhole was not sufficient to cause harm to people. Flame and fragmentation damage should be paid attention to, especially for an underground space with deep depth( h L  ≥ 2 m), large volume, no hinge and light quality manhole cover. The risk assessment method proposed here was applied in H city, and 24, 830 underground spaces with high explosion risk were assessed from 510, 835 underground spaces. Over the past three years, more than 200 dangerous cases of natural gas leaks and accumulations have been identified.